Optimalisasi Poliakrilamida Anionik sebagai Agen Pengendap untuk Mengurangi Ion Tembaga yang Efektif dalam Pengolahan Air Limbah Laboratorium Pendidikan - Munadia Insani; Indang Dewata; Jon Efendi; Eri Barlian; Nurhasan Syah (Postgraduate, University of Mataram, 2025)
This research highlights the potential of anionic polyacrylamide as a main treatment agent for liquid waste from educational laboratories, particularly in the removal of copper ions. This study using experiment with varies the concentration of anionic polyacrylamide with 3, 5, and 7% weight per weight. The initial concentration of copper in liquid waste was very high ranging between 600 mg/L. The findings indicate that the application of anionic polyacrylamide in wastewater treatment significantly reduces the concentration of copper ions, especially in wastewater from educational laboratories. Specifically, anionic polyacrylamide, at a concentration of 3% w/w, effectively removed almost all copper ions from the wastewater found in analytical chemistry laboratory and also achieved the quality standard of treated wastewater for copper parameter. The pH of the treated wastewater is critical in determining the overall effectiveness of the treatment, with a higher pH resulting in more effective coagulation of copper ions. The effectiveness of the treatment is influenced by the pH of the wastewater and the concentration of the polyacrylamide used. Further studies are needed on other types of heavy metals that can be coagulated using this method in order to gain a more comprehensive understanding.